The Effect Of The Jigsaw Type Cooperative Learning Model on Student Learning Outcomes in Review of Student Learning Motivation in Grade IX - Bahctera P Nainggolan; Ropinus Sidabutar; Rianita Simamora (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
The purpose of this study is to determine how the influence of the Jigsaw Type Cooperative Learning Model on Student Learning Outcomes is reviewed from the learning motivation of class IX students at UPTD SMP N 2 Pematangsiantar. The type of research used is Pre-Experiment Design on class IX-2 as the subject in the study and the author uses a quantitative approach. The design used by the researcher is One-Shot Case Study. Based on the results of data analysis and discussion, it can be concluded that there is a positive and significant influence in the use of the Jigsaw Type Cooperative Learning Model on the Learning Outcomes of class IX students at UPTD SMP N 2 Pematangsiantar in the 2025/2026 Academic Year. The positive influence is shown through the regression equation where Y = 43.050 + 1.168 where the value of b = 1.168. The influence is shown through the T-test with Thitung > Ttabel (1.866 > 1.701) or (sig.) < 0.05 (0.000 < 0.05) then Ho is rejected and Ha is accepted which means there is a positive and significant influence of the Jigsaw Type Cooperative Learning Model on Student Learning Outcomes on the material of Quadratic Equations and Functions. The contribution of variable X (Jigsaw Type Cooperative Learning Model) to variable Y (Student Learning Outcomes) is 73.9%.